Sedation for ERCP - Comparison Between Ketamine Diazepam Combination with Propofol Fntanyl Combination (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
For Endoscopic Retrograde Cholangio-pancreatography, an anaesthesiologist usually administers sedation to patient and search for more suitable regimen continues. This prospective randomized study was carried out to compare the efficacy, safety, tolerability and cost effectiveness of ketamine, diazepam combination to propofol, fentanyl combination for sedation during ERCP. One hundred and fifty patients of both sex, age between 18 to 70 years, ASA physical status I and II scheduled to undergo ERCP were included in this study. Patients were randomly allocated into two groups. Group A (n=75) sedated with ketamine 1.5mg/Kg body weight and diazepam 5-10 mg intravenously. Group B (n=75) sedated with propofol 1mg/Kg body weight and fentanyl 1μg/Kg body weight intravenously and intravenous infusion of propofol maintained at 50μg/Kg body weight/min throughout procedure. Both groups showed satisfactory sedating condition for ERCP. Incidences of hypertension and tachycardia were more in group A than group B and differences between two groups were statistically significant (P< 0.01). Agitation and nightmares were found in 10 (13.33%) patients in group A. Mean recovery time was more in group A than group B and difference between two groups was statistically highly significant (P